2001
DOI: 10.1159/000050529
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of D Dimer in Pulmonary Embolism and Pneumonia

Abstract: Background: Diagnosis of pulmonary embolism (PE) and its clear-cut differentiation with other entities of occasional similar presentation remains difficult in routine clinical practice. High plasmatic levels of D dimer (DD), a specific fibrin derivate, have recently been reported in PE. Objective: The purpose of this study was to prospectively evaluate the diagnostic value of plasmatic DD in a clinical setting. Methods: We studied 52 patients with PE proven with pulmonary scintigraphic studies in relation to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It is believed to be a useful marker of abnormal coagulation balance [27] and may be influenced by increased intra-alveolar fibrin deposition [9]. In this study, the plasma D-dimer level was higher in the control group at AE-IPF onset.…”
Section: Discussionmentioning
confidence: 49%
“…It is believed to be a useful marker of abnormal coagulation balance [27] and may be influenced by increased intra-alveolar fibrin deposition [9]. In this study, the plasma D-dimer level was higher in the control group at AE-IPF onset.…”
Section: Discussionmentioning
confidence: 49%
“…They also concluded that d-dimer measurement was useless in the differential diagnosis between pneumonia and PE. 24 Second, a systematic study of the prothrombotic changes in the hemostatic system of patients in whom CAP had been diagnosed was not performed. Prothrombotic changes in the hemostatic system associated with acute inflammation may provide the pathophysiologic link between respiratory infections and vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the diagnostic value of D‐D levels in other disorders is unclear. Some studies have reported an elevation of D‐D levels in CAP, 6 but whether D‐D levels predict risk in these patients is still unclear. CRP, an acute phase protein, is a sensitive marker of inflammation 7 .…”
Section: Introductionmentioning
confidence: 99%